Congenital Toxoplasmosis in Humans and Domestic Animals - Bresciani, Katia Denise Saraiva; Da Costa, Alvimar José (Bentham Science Publishers, 2018)
"Congenital Toxoplasmosis in Humans and Domestic Animals presents information about Toxoplasma gondii and its infection in neonates and different animals (cats, cattle, dogs, goats, pigs and sheep). Readers will have quick access to the pathophysiology, diagnosis, reproductive disorders (such as abortion, neonatal mortality and prematurity) and treatment of both human and veterinary toxoplasmosis. In addition, important aspects for control programs of congenital toxoplasmosis and for maternal and neonatal screening in such control programs are discussed. Thus readers will be better equipped to conduct prevention programmes and routine diagnosis of zoonotic infections related to T. gondii. This handbook is of interest to epidemiologists, doctors, veterinarians and public health specialists."--